2019
DOI: 10.3126/jer.v8i1.25478
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Education Decentralization and 'Sustained' Elite Capture – Explicating Cases From Two Public Schools

Abstract: The paper aims at uncovering the practices of educational decentralization in Nepal that started after the restoration of democracy in 1990. Though decentralization in education in Nepal began with the aim of greater community participation and autonomy to the needs and priorities perceived by the local level functionaries in school, it has been subject to elite capture in its governance. Because of control in planning, organization, management, financial liability and different activities for the education sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…There highlight some barriers of participating in decision making are age, sex, qualification, childcare and family responsibilities, lack of partner support, workplace environment, harassment and violence, lack of knowledge. Furthermore, the women participation decision making is still questionable because head teachers capture single power ofdecision in own hand and do not discuss the financial and other major issues with teachers, parents and students, or take a few powerful SMC members in hand, and dominate the decision-making process (Dhakal, 2017(Dhakal, , 2019Hamal, 2018).…”
Section: Literature On Women Participation In Public Institutions In ...mentioning
confidence: 99%
See 3 more Smart Citations
“…There highlight some barriers of participating in decision making are age, sex, qualification, childcare and family responsibilities, lack of partner support, workplace environment, harassment and violence, lack of knowledge. Furthermore, the women participation decision making is still questionable because head teachers capture single power ofdecision in own hand and do not discuss the financial and other major issues with teachers, parents and students, or take a few powerful SMC members in hand, and dominate the decision-making process (Dhakal, 2017(Dhakal, , 2019Hamal, 2018).…”
Section: Literature On Women Participation In Public Institutions In ...mentioning
confidence: 99%
“…But in our patriarchal societies women are not conceptualized as holding power, wielding power, being powerful (Barriteau, 2003). Furthermore, the women participation in decision making is still questionable and are dominated the decision-making process (Dhakal, 2017(Dhakal, , 2019Hamal, 2018). Almost management committees are male dominated and women have represented for only to fill the legal gap.…”
Section: Gender Bias In Smcmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, SMC in the Nepali community the school governance system appears to be a 'formal' committees, and thus they are excluded in the governance process. Moreover, studies (Dhakal, 2019;Mncube, 2009) have reported that meaningful participation of the stakeholders in educational decision making is still questioned, especially because Headteachers (HTs) singlehandedly make decisions, and do not discuss financial activities with teachers, parents and students, or take a few powerful SMC members in hand, and dominate the decision-making process-leading to 'sustained elite capture' (Dhakal, 2017;Hamal, 2018). As the most influential and active body of school governance, it is important to see SMC in an organisational context in which the politics and economy besides sociology of human thinking affect how SMC members perceive themselves, and those they work with, as well as how other stakeholders perceive their roles.…”
mentioning
confidence: 99%